Improving slum life urban poverty in Bangladesh - Griffiths, Steven (Asian Development Bank, 1996)
When the harvest is over, millions of Bangladesh's landless agricultural laborers face unemployment and hunger. Driven by poverty and scarcity, many migrate to urban centers in search of a better life. Yet this constant urban migration has led to a proliferation of congested city slums. Without running water and basic sanitation services, these communities inadequately house the country's urban poor. In Dinajpur, an innovative slum improvements project is demonstrating a way forward. The project is providing critical social and physical infrastructure, and skills training for community residents. The project may serve as a model for others, allowing slum dwellers to lead healthier, happier and more productive lives.